Nghiên cứu chế tạo tinh thể nano kim loại đồng bằng phương pháp hoàn nguyên ở nhiệt độ thấp nhằm ứng dụng trong nông nghiệp - Chi, Trần Quế; Sơn, Vũ Hồng; Sơn, Lê Phúc; Trung, Nguyễn Quốc; Chân, Đỗ Thế; Hương, Trần Thị; Hoàng Yến, Quách Thị; Toàn, Nguyễn Thị; Nhung, Nguyễn Hồng; Nam, Bùi Quốc; et al. (Vietnam Journal of Chemistry, 2014)
Copper nanoparticles were prepared by hydrogen reduction by electrolysis of water. The formation, structure and morphology of products were characterized by X-ray diffraction analysis (XRD), Scanning Electron Microscope (SEM) and the specific surface area (BET) was determined by N2 physisorption Brunauer - Emmitt - Teller (BET) method. The results showed that copper particles are a simple phase and the size about 40-70 nm, the BET-surface area as 15.85 m2/g. The data showed that copper nanoparticles increased germination rate of maize at normal condition. Keywords: Copper nanoparticles, reverting method.